The Experience of Tinnitus and Its Interaction With Unique Life Histories—Life Events, Trauma and Inner Resources Narrated by Patients With Tinnitus - Erlandsson, Soly Inga-Maj; Lundin, Linda; Dauman, Nicolas (Frontiers in Psychiatry, 2020)
Abstract Background: The challenges facing people with chronic tinnitus are to rebuild quality of life and restore future hope. Previous harsh experiences including traumatic episodes can hamper adjustment and prolong suffering. Recovery is thus not about eliminating the symptoms; instead it is about reducing aggravating reactions and recovering social roles, relationships and interests. The main goal of the study was to enhance the foundation for making a choice about treatment by focusing on how tinnitus interacts with the participants’ unique life histories. Method: Four women and one man in the ages of 52 – 58 took part in the study. They had consulted a special hearing clinic in Sweden for annoying tinnitus. Criteria for inclusion were: (i) that tinnitus was regarded as a problem (ii) with negative consequences for quality of life and (iii) that the participants were willing to share these experiences with the researchers during three interview occasions. Narrative methodology was employed in order to achieve the goals of the study. Results: Based on the analysis, the main structure of three participants’ narratives were regressive with a pessimistic tone. The main structure of the remaining two participants’ narratives were stable with an objective tone and progressive accompanied by an optimistic tone. The findings revealing that three out of five participants in our study presented a regressive form of narrative indicate ongoing struggles beyond tinnitus itself, which they were unable to bring to closure. Study results implies that a central issue in rehabilitation should be to help suffering patients to overcome rumination and unresolved conflicts and thereby extend their ability for full commitment in life. Conclusion: Considering enduring tinnitus as a chronic condition, whose course may vary depending on the patient’s general health status, an alteration of progressive and stable narratives is likely to occur during the lifespan. A progressive narrative shows similarities to the core construct of the salutogenesis model of health promotion (Antonovsky, 1996). In conclusion, a narrative approach in tinnitus rehabilitation can be health promoting by offering the patient the opportunity to engage in storytelling which in turn can increase comprehensibility and sense of coherence.